2021
DOI: 10.3389/fcell.2020.619079
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA Aerrie Controls DNA Damage Repair via YBX1 to Maintain Endothelial Cell Function

Abstract: Aging is accompanied by many physiological changes. These changes can progressively lead to many types of cardiovascular diseases. During this process blood vessels lose their ability to maintain vascular homeostasis, ultimately resulting in hypertension, stroke, or myocardial infarction. Increase in DNA damage is one of the hallmarks of aging and can be repaired by the DNA signaling and repair system. In our study we show that long non-coding RNA Aerrie (linc01013) contributes to the DNA signaling and repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 69 publications
1
35
0
Order By: Relevance
“…Linc01013 is also known as Age and EndMT regulated RNA in endothelium (Aerrie) ( Pham et al, 2020 ). The function of linc01013 is poorly characterized.…”
Section: Long Noncoding Rnas In Cellular Senescence Of Vascular Endotheliummentioning
confidence: 99%
See 4 more Smart Citations
“…Linc01013 is also known as Age and EndMT regulated RNA in endothelium (Aerrie) ( Pham et al, 2020 ). The function of linc01013 is poorly characterized.…”
Section: Long Noncoding Rnas In Cellular Senescence Of Vascular Endotheliummentioning
confidence: 99%
“…The function of linc01013 is poorly characterized. Recently, it was revealed that its expression was induced by oscillatory flow and aging in HUVECs, and induced in atherosclerotic plaques from symptomatic patients compared to asymptomatic patients and in ischemic heart tissues from the left ventricle ( Pham et al, 2020 ). Loss of Aerrie impaired cellular migration, barrier function, and angiogenic sprouting of HUVECs ( Pham et al, 2020 ).…”
Section: Long Noncoding Rnas In Cellular Senescence Of Vascular Endotheliummentioning
confidence: 99%
See 3 more Smart Citations